Improving your reading skills - Wilson, Nancy Roebuck; Conway, Seth; Educational Video Network, Inc. (Huntsville, Tx. : Educational Video Network, Inc.)
This video will helps in preparing the mind for reading, determining objectives, schedule reading to match attention span, learn to recognize organizational methods, read actively and remembering what already read
Title from title screen
Executive editor, Anne Russell ; executive producer, George H. Russell ; videography, Seth Conway ... [et al.] ; editor, Seth Conway
Narrator: Thomas Soare
Keywords: Reading comprehension; Deveopmental reading